KEGIATAN BTA SEBAGAI PEMBENTUKAN KARAKTER SISWA YANG ISLAMI DI SMP MUHAMMADIYAH 4 SAMBI BOYOLALI - Putri Gayatri Ramadhanty; Indah Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The implementation of Al-Qur'an reading and writing activities at SMP Muhammadiyah 4 Sambi Boyolali is carried out from Tuesday to Thursday, which is carried out after teaching and learning activities. This activity must be carried out by all students and students based on their abilities. For reading and writing Al-Quran Iqro 'takes place in each student's class, while for reading and writing Al-Quran and Tahfidz takes place in the mosque around the school. Application of Read and Write Al-Quran is the right way to form an Islamic character in oneself. Among the series of activities to read and write Al-Qur'an, the teacher always provides motivation, guidance and responsibility to students. The person in charge of reading and writing Al-Qur'an activities is the walikelas who holds each grade level. The series of activities to read and write Al-Qur'an are mandatory for students at SMP Muhammadiyah 4 Sambi because it is a work program of the school principal himself to shape the behavior and character of students who draw closer to Allah SWT. Islamic student character can be formed in a student by practicing good life habits and always worshiping Allah SWT.